مكانة المعاهدات الدولية في النظام القانوني الجزائري - إيمـــــــــــــان علــــــوي; عائشــــــة حـــــــــــــزام (My University, 2021)
Summary International treaties are the most prominent means in the international arena of strengthening and supporting links between the components of the international community international law ", which is at the forefront of public international law in regulating international relations, Every State has adopted a platform for its incorporation into its legal system. Algerian legislation regulates this by virtue of article 154 of the Constitution, by virtue of the Convention's primacy over domestic legislation, which is binding on all, in accordance with the guarantees of its primacy. .................. ملخص تعتبر المعاهدات الدولية الوسيلة الأبرز في الساحة الدولية لتقوية ودعم الروابط بين مكونات المجتمع الدولي، فهي تحتل مركز الصدارة في مصادر القانون الدولي العام إذ تعمل على تنظيم العلاقات الدولية، فكل دولة اعتمدت منهاجا للإدماجها ضمن النظام القانوني لها، فالمشرع الجزائري نظم ذلك بموجب المادة 154 من الدستور وذلك بسمو الاتفاقية على التشريع الداخلي فهي ملزمة في مواجهة الكافة وذلك وفقًا لضمانات سمو المعاهدة. .................. Résumé Les traités internationaux sont le moyen le plus important sur la scène internationale de renforcer et de soutenir les liens entre les composantes du droit international de la communauté internationale ", qui est à l’avant-garde du droit international public dans la réglementation des relations internationales, chaque Etat a adopté une plate-forme pour son intégration dans son système juridique. La législation algérienne le règle en vertu de l’article 154 de la Constitution, en vertu de la primauté de la Convention sur la législation nationale, qui est contraignante pour tous, conformément aux garanties de sa primauté.